Unique Cellular and Biochemical Features of Human Mitochondrial Peroxiredoxin 3 Establish the Molecular Basis for Its Specific Reaction with Thiostrepton - Kimberly J. Nelson; Terri Messier; Stephanie Milczarek; Alexis Saaman; Stacie Beuschel; Uma Gandhi; Nicholas Heintz; Terrence L. Smalley; W. Todd Lowther; Brian Cunniff (MDPI AG, 2021)
A central hallmark of tumorigenesis is metabolic alterations that increase mitochondrial reactive oxygen species (mROS). In response, cancer cells upregulate their antioxidant capacity and redox-responsive signaling pathways. A promising chemotherapeutic approach is to increase ROS to levels incompatible with tumor cell survival. Mitochondrial peroxiredoxin 3 (PRX3) plays a significant role in detoxifying hydrogen peroxide (H2O2). PRX3 is a molecular target of thiostrepton (TS), a natural product and FDA-approved antibiotic. TS inactivates PRX3 by covalently adducting its two catalytic cysteine residues and crosslinking the homodimer. Using cellular models of malignant mesothelioma, we show here that PRX3 expression and mROS levels in cells correlate with sensitivity to TS and that TS reacts selectively with PRX3 relative to other PRX isoforms. Using recombinant PRXs 1-5, we demonstrate that TS preferentially reacts with a reduced thiolate in the PRX3 dimer at mitochondrial pH. We also show that partially oxidized PRX3 fully dissociates to dimers, while partially oxidized PRX1 and PRX2 remain largely decameric. The ability of TS to react with engineered dimers of PRX1 and PRX2 at mitochondrial pH, but inefficiently with wild-type decameric protein at cytoplasmic pH, supports a novel mechanism of action and explains the specificity of TS for PRX3. Thus, the unique structure and propensity of PRX3 to form dimers contribute to its increased sensitivity to TS-mediated inactivation, making PRX3 a promising target for prooxidant cancer therapy.